2000
DOI: 10.1185/0300799019117004
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of Breast Cancer: An Overview

Abstract: The role of lifestyle modifications, antioestrogens, cyclo-oxygenase-2 inhibitors and prophylactic mastectomy in reducing breast cancer is reviewed. It is concluded that avoiding postmenopausal obesity and regular physical activity are simple measures that seem to reduce breast cancer risk. There is no conclusive evidence that dietary modification and vitamin supplementation significantly reduce the risk of breast cancer. The evidence suggests that tamoxifen significantly reduces the risk of breast cancer in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Reports of an association between diet and breast cancer are inconsistent. Prospective studies, including some intervention studies, have not found consistent evidence of any association between dietary factors and breast cancer . This meant that diet was not considered further as a modifiable risk factor for breast cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of an association between diet and breast cancer are inconsistent. Prospective studies, including some intervention studies, have not found consistent evidence of any association between dietary factors and breast cancer . This meant that diet was not considered further as a modifiable risk factor for breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34] Use for 5 years or more increases the risk of breast cancer by about 35%, with the risk returning to normal 5 years after stopping HRT. 16,25,32 There is a 66% increased risk of breast cancer for current use of HRT compared with the not used category; RR 1.7 (1.6-1.8). 35…”
Section: Hrtmentioning
confidence: 99%
“…Nonsteroidal anti-inflammatory drugs (NSAIDs), which act through inhibition of cyclooxygenase enzyme (COX), are one such class of drugs that have been studied for their possible role in breast cancer prevention. Epidemiological studies investigating the relationship between NSAID use and breast cancer have reported conflicting results; some studies [3][4][5] show 30-40% reduction in breast cancer incidence with NSAID use, whereas others failed to confirm this relationship. 6,7 NSAIDs work by inhibiting both constitutive and inducible cyclooxygenase enzymes (COX-1 and COX-2, respectively), both of which have been postulated to play a role in carcinogenesis.…”
mentioning
confidence: 99%
“…11 The cyclooxygenase enzymes are involved in prostaglandin synthesis; prostaglandin E2 (PGE2) is an important mediator of tumorigenesis. 12,13 PGE2 acts by binding to one of four separate receptors, EP 1 through EP 4 , which are members of the rhodopsintype receptors coupled to hetero-trimeric GTPbinding proteins. 14 Activation of EP 1 and EP 3 receptors leads to increased intracellular calcium and decreased cyclic AMP levels.…”
mentioning
confidence: 99%
“…For example, several lines of evidence suggest that there is a connection between COX-2, obesity, and cancer (Leris and Mokbel, 2001;Na and Surh, 2003;Raju and Bird, 2003). Products of COX-2 have been shown to promote cellular proliferation and angiogenesis.…”
Section: Implications For the Pathophysiology Of Diseasementioning
confidence: 95%